2019
DOI: 10.1155/2019/5862985
|View full text |Cite
|
Sign up to set email alerts
|

Donor Small-Droplet Macrovesicular Steatosis Affects Liver Transplant Outcome in HCV-Negative Recipients

Abstract: Background. No data are available on liver transplantation (LT) outcome and donor liver steatosis, classified as large droplet macrovesicular (Ld-MaS), small-droplet macrovesicular (Sd-MaS), and true microvesicular (MiS), taking into account the recipient Hepatitis C virus (HCV) status. Aim. We investigate the impact of allograft steatosis reclassified according to the Brunt classification on early graft function and survival after LT. Methods. We retrospectively reviewed 204 consecutive preischemia biopsies o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 36 publications
0
11
0
Order By: Relevance
“…Notably, small droplet macrosteatosis is associated with reduced hepatic ATP content and poorer outcomes in liver transplant patients, suggesting a link to mitochondrial dysfunction (Ferri et al, 2019). Previously, we have shown that alcohol impairs mitochondrial bioenergetics (Young et al, 2006;King et al, 2014) and damages mtDNA (Venkatraman et al, 2004), with other studies reporting clock control of mitochondrial function (Peek et al, 2013;Jacobi et al, 2015).…”
Section: Dmentioning
confidence: 77%
“…Notably, small droplet macrosteatosis is associated with reduced hepatic ATP content and poorer outcomes in liver transplant patients, suggesting a link to mitochondrial dysfunction (Ferri et al, 2019). Previously, we have shown that alcohol impairs mitochondrial bioenergetics (Young et al, 2006;King et al, 2014) and damages mtDNA (Venkatraman et al, 2004), with other studies reporting clock control of mitochondrial function (Peek et al, 2013;Jacobi et al, 2015).…”
Section: Dmentioning
confidence: 77%
“…Steatotic liver is a common type of ECD. However, such organs are more prone to preservation injury and graft dysfunction, resulting in a poor prognosis after liver transplantation 6‐8 . It has been proposed that steatotic livers are more susceptible to ischaemia‐reperfusion (I/R) injury, which impairs liver regeneration and is a major cause of liver damage 6,9 .…”
Section: Introductionmentioning
confidence: 99%
“…Permanent histological sections were analyzed to assess and classify the donor liver steatosis according to the Brunt classification [ 3 , 4 , 48 ]: Ld-MaS, as one or few large vacuoles in the cytoplasm with nuclear displacement in an eccentric location of the cell; Sd-MaS, as few and discrete fat vacuoles that were smaller than half of the cell and did not displace the nucleus ( Figure 2 ). True microvesicular steatosis was defined as the presence of innumerable tiny indiscernible lipid vesicles diffusely distributed in the cytoplasm causing its foamy appearance as previously illustrated also by Ferri et al [ 49 ]. The extent of each type of steatosis was expressed as a percentage of each type of steatotic hepatocyte compared to all hepatocytes.…”
Section: Methodsmentioning
confidence: 99%